Calcium signalling in developing cardiomyocytes: implications for model systems and disease. (9th February 2015) - Louch, William E.; Koivumäki, Jussi T.; Tavi, Pasi
Abstract : Abstract: Adult cardiomyocytes exhibit complex Ca 2+ homeostasis, enabling tight control of contraction and relaxation. This intricate regulatory system develops gradually, with progressive maturation of specialized structures and increasing capacity of Ca 2+ sources and sinks. In this review, we outline current understanding of these developmental processes, and draw parallels to pathophysiological conditions where cardiomyocytes exhibit a striking regression to an immature state of Ca 2+ homeostasis. We further highlight the importance of understanding developmental physiology when employing immature cardiomyocyte models such as cultured neonatal cells and stem cells.